Intracellular management of information: from DNA to proteins - Juan M. Lara (tripleC: Communication, Capitalism & Critique)
The living features of cells constitute an information flow from a central database, the nuclear DNA, to molecular effectors, proteins, which are synthesised in the cytoplasm. This flow comprises two changes in information units: transcription and translation. Transcription is carried out in the nucleus and consists in the transduction of specific instructions from the DNA to an intermediary, the RNA, which in its canonical form is a messenger (mRNA) that takes information from the cell nucleus. In the cytoplasm, information in the messenger gives the commands for a specialised molecular complex to build a specific protein. After regulation of the form, proteins are integrated as structural and/or functional units in the complex network of biological functions in the cell.